Fire testing of the building facade insulated with foam polystyrene/Putų polistirenu apšiltintų fasado fragmentų gaisriniai bandymai - Nyderis, Albertas; Mačiulaitis, Romualdas (Journal of Civil Engineering and Management, 1999)
In the past decade, construction business applied various heat insulating materials comprising a spectrum of properties according to their combustibility. Particular attention was paid to insulation materials related to fire hazards. The normative fire safety documents started to be drawn up in this country at the time when the process of building insulation had not been initiated yet. Therefore, there still exists a great need for assessing the fire hazards of building insulation systems. With the use of the experience of other countries new testing equipment for insulating building facade with foam polystyrene has been recently established. The equipment is loaded with a 2.4×2.0 meter wall fragment and 800×700 mm plate of electrical thermal radiation flow, as well as a gas burner and a device for taking the temperature. The theoretical bottom-line of these testing methods lies in the heat exchange between two parallel walls, one of which is much hotter. The calculation of the thermal radiation flow is presented in formula 1 and the theoretical basis is indicated in formulae 2–10. Formula 11 indicates the rates of the flame heat radiation flows. Formula 12 shows special testing conditions. In the course of testing the insulation systems, the geometrical quantities of violation zones of foam polystyrene have been determined, they have exceeded the calculations of the flow radiation plate of active heat several times. A strong functional relation between the thickness of foam polystyrene and the rates of violation zones (rxy =0.694) and a weak functional relation between the thickness of plaster and the rates of violation zones (rxy = −0.580) have also been defined. Formulas 13 and 14 describe the relations between the surface areas of the destruction, the thickness of the foam polystyrene and the thickness of the plaster. By taking the temperatures in the vertical axis of the geometrical centre of the wall fragment, it was determined that in the course of testing the temperatures become dangerous in relation to the combustibles (about 250°C). The tests indicate that favourable and stable testing conditions established. It is expedient to continue the tests with other types of building facade materials.Article in Lithuanian.First Published Online: 26 Jul 2012